Rating the Delivery Rate of TETfund Projects in South-East Nigerian State Universities - Nnadi, Ezekiel Ejiofor; Omerhi, Oghenetega John; Boniface, Nancy Amarachi (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
The study evaluates the completion rates of Tertiary Education Trust Fund (TETfund) projects in South-East State Universities, highlighting the importance of timely completion for high-quality education and university infrastructure development in Nigeria's impoverished economic situation, where inadequate funding is common. The study was conducted in five South-East Nigerian state universities targeting the 6662 population. The analysis used SPSS, resulting in 35.5% of the sample. The results showed that the duration of Tertiary Education Trust Fund (TETfund) projects has influenced project completion rates in South-East Nigerian universities. 28% of respondents believe that time duration has led to some universities losing TETfund project approval, while 42% believe it has increased the likelihood of receiving more projects from TETfund. The test hypotheses confirmed that TETfund time duration has significant positive effect on the completion rate of projects. The model summary showed that time duration has caused some state universities to lose TETfund project approval, while it has continued to give universities the chance for more projects from TETfund. The study also highlighted the role of time to TETfund in ensuring projects approved must be completed at the appropriate time, which it assumes. The results showed that the F-value is the Mean Square Regression (3863.049), which is statistically significant (Sig =.000). The study suggests that State University management should maintain TETfund project duration due to high Federal Government funds and enforce stronger rules for project quality.